Hypothesis: JNK signaling is a therapeutic target of neurodegenerative diseases - Zhao, Yingying; Kuca, Kamil; Wu, Wenda; Wang, Xu; Nepovimova, Eugenie; Musilek, Kamil; Wu, Qinghua (Alzheimer's & dementia, 2022)
The exact signaling leading to neurological dysfunction in neurodegenerative diseases is currently unknown. We hypothesize that the c-Jun N-terminal kinase (JNK) signaling pathway is a potential therapeutic target for neurodegenerative diseases. This postulate rests on extensive data from cell and animal experimental studies, demonstrating that JNK signaling plays a crucial role in the pathogenesis of neurodegenerative diseases. The sustained activation of JNK leads to synaptic dysfunction and even neuronal apoptosis, ultimately resulting in memory deficits and neurodegeneration. JNK phosphorylates the amyloid precursor protein and tau, ultimately resulting in the formation of extraneuronal senile plaques and intraneuronal neurofibrillary tangles. Our hypothesis could be validated by investigating the cerebral cortex of elderly chimpanzees injected with phosphorylated JNK or transgenic pig and chimpanzee models established using gene editing technology including CRISPR. This hypothesis provides clues for further understanding the molecular mechanisms of neurodegenerative diseases and the development of potential target therapeutic drugs.
Keywords: proteiny tau; JNK mitogenem aktivované proteinkinasy; lidé; neurodegenerativní nemoci; prasata; Amyloid beta-Peptides; Pan troglodytes; amyloidní beta-protein; tau; Neurons; Alzheimerova nemoc; mozková kůra; Phosphorylation; Signal Transduction; Humans; neurony; genový targeting; fosforylace; tau Proteins; Swine; Disease Models, Animal; signální transdukce; Gene Targeting; amyloid beta; Alzheimer Disease; Neurodegenerative Diseases; zvířata; Cerebral Cortex; JNK; amyloidový prekurzorový protein beta; Animals; JNK Mitogen-Activated Protein Kinases; Amyloid beta-Protein Precursor; neurodegenerative diseases; modely nemocí na zvířatech; Alzheimer's disease